2013
DOI: 10.1017/s0959269513000057
|View full text |Cite
|
Sign up to set email alerts
|

Beyond advanced stages in high-level spoken L2 French

Abstract: The aim of this study is twofold: first, to find evidence for additional advanced stages in L2 French. The continuum of Bartning and Schlyter (2004) is taken as a point of departure. It is hypothesized that a number of linguistic criteria will account for high-level proficiency. It was earlier found that besides morpho-syntax, formulaic sequences and information structure are interesting phenomena for highly proficient learners (Bartning, Forsberg and Hancock, 2009). Three more measures are now added, i.e. per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
(84 reference statements)
1
10
0
Order By: Relevance
“…Very high scores, on the other hand, were obtained by several interviewees with AOs below 12. This qualitative analysis of the grammatical complexity scores supports previous research that has found AO effects, particularly when grammar and other formal aspects of the lexicon are investigated (e.g., Abrahamsson & Hyltenstam, 2009;Forsberg-Lundell et al, 2013). A different picture emerged for lexical complexity.…”
Section: Age Of Onsetsupporting
confidence: 85%
See 3 more Smart Citations
“…Very high scores, on the other hand, were obtained by several interviewees with AOs below 12. This qualitative analysis of the grammatical complexity scores supports previous research that has found AO effects, particularly when grammar and other formal aspects of the lexicon are investigated (e.g., Abrahamsson & Hyltenstam, 2009;Forsberg-Lundell et al, 2013). A different picture emerged for lexical complexity.…”
Section: Age Of Onsetsupporting
confidence: 85%
“…The present study applied the Complexity, Accuracy, and Fluency (CAF) approach, most frequently used in the assessment of beginning to advanced stages of L2 acquisition in classroom-based settings (Housen, Kuiken, & Vedder, 2012), to investigate advanced L2 proficiency. It thereby contributes to the small body of existing CAF research targeting productive L2 grammatical and lexical complexity in naturalistic settings beyond the advanced stage of L2 development (e.g., Forsberg Lundell et al, 2013;Forsberg Lundell & Lindqvist, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from studies such as these suggest that sufficient exposure to and use of the L2 can lead to nativelike acquisition of interface phenomena, although perhaps only at the very highest levels of L2 proficiency. If it is the case that such interfaces are mastered very late in L2, by only those speakers who progress beyond "advanced" levels (see Forsberg Lundell et al, 2014), it further underscores the importance of careful proficiency assessments of purported NNSs.…”
Section: Near-nativenessmentioning
confidence: 99%